Posterior composite restoration update: focus on factors influencing form and function - Bohaty BS; Ye Q; Misra A; Sene F; Spencer P (Dove Medical Press, 2013)
Brenda S Bohaty,1,2 Qiang Ye,3 Anil Misra,3,4 Fabio Sene,6 Paulette Spencer3,51Department of Pediatric Dentistry, University of Missouri-Kansas City School of Dentistry, Kansas City, MO, USA; 2Department of Pediatric Dentistry, Children's Mercy Hospital, Kansas City, MO, USA; 3Bioengineering Research Center, 4Department of Civil, Environmental, and Architectural Engineering, 5Department of Mechanical Engineering, University of Kansas, Lawrence, KS, USA; 6Department of Restorative Dentistry, State University of Londrina, School of Dentistry, Londrina, BrazilAbstract: Restoring posterior teeth with resin-based composite materials continues to gain popularity among clinicians, and the demand for such aesthetic restorations is increasing. Indeed, the most common aesthetic alternative to dental amalgam is resin composite. Moderate to large posterior composite restorations, however, have higher failure rates, more recurrent caries, and increased frequency of replacement. Investigators across the globe are researching new materials and techniques that will improve the clinical performance, handling characteristics, and mechanical and physical properties of composite resin restorative materials. Despite such attention, large to moderate posterior composite restorations continue to have a clinical lifetime that is approximately one-half that of the dental amalgam. While there are numerous recommendations regarding preparation design, restoration placement, and polymerization technique, current research indicates that restoration longevity depends on several variables that may be difficult for the dentist to control. These variables include the patient's caries risk, tooth position, patient habits, number of restored surfaces, the quality of the tooth–restoration bond, and the ability of the restorative material to produce a sealed tooth–restoration interface. Although clinicians tend to focus on tooth form when evaluating the success and failure of posterior composite restorations, the emphasis must remain on advancing our understanding of the clinical variables that impact the formation of a durable seal at the restoration–tooth interface. This paper presents an update of existing technology and underscores the mechanisms that negatively impact the durability of posterior composite restorations in permanent teeth.Keywords: composites, bonding, dental restorations